National – cultural specificity of phraseological units: Национально - культурная специфика фразеологизмов (Journal of the College of Languages (JCL), 2021)
The present article studies the specific cultural features contained in phraseological units. The problem is approached through three different levels:The modern linguistic meaning.Lexical components of phraseological units.The first variables of linguistic units. The paper emphasizes the gradual process of the cultural charge in the semantic structure of phraseological units. Наша Статья посвящена вопросам анализа национ-ально - культурной специфики ФЕ . Это проблема рассмат-ривается на трех уровнях:1) в совркупном фразеологич-еском значении,2) в значении отдельных лексических компонентов ФЕ,3) в значении переменного прототипа ФЕ.Мы здесь подчеркиваем , что градуальный характер проявления национально – специфичной информации, закодированной в значени Фразеологизмов.